2021
DOI: 10.3390/ijms23010075
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Homer1a and Homer2 Isoform Expression Is a Key Mechanism for Muscle Soleus Atrophy in Spaceflown Mice

Abstract: The molecular mechanisms of skeletal muscle atrophy under extended periods of either disuse or microgravity are not yet fully understood. The transition of Homer isoforms may play a key role during neuromuscular junction (NMJ) imbalance/plasticity in space. Here, we investigated the expression pattern of Homer short and long isoforms by gene array, qPCR, biochemistry, and laser confocal microscopy in skeletal muscles from male C57Bl/N6 mice (n = 5) housed for 30 days in space (Bion-flight = BF) compared to mus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In previous studies, we showed that Homer protein family members are conserved in healthy mouse, rat, and human skeletal muscles, and are particularly localised at the postsynaptic microdomain, where they play a key role in coordinating the neuromuscular signal transduction machinery in a mechanism dependent on nerve and muscle activity [ 2 , 9 ]. We therefore set out to study the expression pattern of Homer genes and postsynaptic subcellular localisation in MG-affected skeletal muscles to find out whether they are linked to a proper expression and function of the nicotinic acetylcholine receptor (nAChR) in disease-affected peripheral synapsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we showed that Homer protein family members are conserved in healthy mouse, rat, and human skeletal muscles, and are particularly localised at the postsynaptic microdomain, where they play a key role in coordinating the neuromuscular signal transduction machinery in a mechanism dependent on nerve and muscle activity [ 2 , 9 ]. We therefore set out to study the expression pattern of Homer genes and postsynaptic subcellular localisation in MG-affected skeletal muscles to find out whether they are linked to a proper expression and function of the nicotinic acetylcholine receptor (nAChR) in disease-affected peripheral synapsis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed that Homer protein family members are conserved in healthy mouse, rat, and human skeletal muscles, and are particularly localised at the postsynaptic microdomain, where they play a key role in coordinating the neuromuscular signal transduction machinery in a mechanism dependent on nerve and muscle activity [2,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Blottner et al [ 6 ] conducted a study to investigate the expression pattern of Homer short and long isoforms in the skeletal muscles of male C57Bl/N6 mice after 30 days in space compared to ground-housed animals and rats subjected to hindlimb unloading. The results showed an increase in Homer1a transcripts and the downregulation of Homer2 long-form in the soleus muscle of animals exposed to microgravity or hindlimb unloading, suggesting the possible role of Homer isoforms in neuromuscular junction imbalance/plasticity.…”
mentioning
confidence: 99%